Determination of stress and strain concentrations in the elastic-plastic materials under bending and torsion - Kurek, M.; Łagoda, T.; Warmuzek, P. (Фізико-хімічна механіка матеріалів, 2011)
The analysis of stress and strain concentrations of constructional materials subjected to bending and torsion is presented. The known methods of stress determination for any elastic-plastic material assume the linear strain concentration under bending and torsion. Determination of stress and strain concentrations and their presentation as graphs were the main aims of this paper. Five materials were tested. They had different cyclic strain curves, and were loaded by the torsional and bending moments. The results proved a linear character of the strain distribution for any material in the all applied loading range. Визначено розклад напружень і деформацій в перетині проаналізованого елемента вальців та подано графічно за допомогою комп’ютерної моделі. Аналіз п’яти матеріалів та їх кривих циклічного деформування з різними характеристиками за умов кручення та згину показав лінійний характер розкладу деформацій для кожного з них за всіх прикладених навантажень. Определено распределение напряжений и деформаций в сечении проанализированного элемента валков и представлено графически с помощью компьютерной модели. Анализ пяти материалов и их кривых циклического деформирования с разными характеристиками при кручении и изгибе показал линейный характер распределения деформаций для каждого из них при всех приложенных нагрузках.